Challenging assumptions about habit: A response to Hagger (2019). (March 2020) - Phillips, L. Alison
Abstract: Widely cited literature assumes habits to be: (1) specific and rigid behavioral responses; (2) in response to location- and timing-stable, external contexts, (3) goal-independent, and (4) enacted without conscious awareness. Hagger (2019) recently reviewed this literature as it applies to the physical activity domain. The purpose of this article is to challenge these assumptions in favor of a habit conceptualization that is more applicable to physical activity: (1) behavioral instigation and/or execution can be habitual, allowing for variable responses to cues; (2) stable contexts can be internal or functional (cued by a preceding action) but may vary in timing and physical location; (3) a shift from external to internal goal dependence may characterize habit development; and (4) types of automaticity other than purely nonconscious enactment may characterize habitual action. I present theory and research that supports these alternative characterizations and discuss their ramifications for physical activity adoption and maintenance via habit.